PELAKSANAAN TUGAS PEMBIMBING KEMASYARAKATAN DALAM PROSES DIVERSI ANAK YANG BERKONFLIK DENGAN HUKUM DI BALAI PEMASYARAKATAN KELAS I MEDAN - Karina, Ica (Universitas Katolik Santo Thomas Medan, 2020)
Community advisors are correctional officers at the Correctional Center who provide guidance to residents assisted by correctional facilities outside the authority of prisons. In the juvenile justice process, community supervisors in making reports on the results of community research (LITMAS). This social research serves to take a closer look at the background of children's social life in terms of economy, education, interactions and social interactions. The function of criminalization is no longer just a deterrent but also a process of social rehabilitation and reintegration of the Assisted People in prisons. In this investigation, it shows that the task of Community Guidance in making social research and assisting children in conflict with the law as suspects / defendants in juvenile criminal justice processes, and for adult suspects in certain criminal acts and LITMAS for the benefit of treating prisoners and coaching prisoners shows Community Guidance since the beginning Pelaksanaan Tugas Pembimbing Kemasyarakatan Dalam Proses Diversi Anak Yang Berkonflik Dengan Hukum di Balai Pemasyarakatan Kelas 1Â of the legal process until the return of a prisoner and correctional protege to the community. In its implementation, the Class I Medan social adviser has duties and functions, including the main task of the Bapas Class I Medan social adviser, which is to provide community guidance or alleviation of children in accordance with the invitation regulations who carry out and carry out coaching, guidance and supervision of clients outside the Penitentiary.